Pennsylvania Archives. October 14-1756-January 3, 1764 - Hoban, Charles F. (s.n., 1935)
A collection of documents supplementing the companion series known as "Colonial records," which contain the Minutes of the Provincial council, of the Council of safety, and of the Supreme executive council of Pennsylvania.
Under the Direction of Lester K. Ade Superintendent of Public Instruction [3rd Prinicipal of the New Haven Normal School]
Keywords: History; Pennsylvania; Periodicals; Periodicals; Pennsylvania; Sources; unidentified